Is uniportal thoracoscopic surgery a feasible approach for advanced stages of non-small cell lung cancer? - Gonzalez-Rivas, Diego; Fieira, Eva; Delgado, Maria; Mendez, Lucía; Fernandez, Ricardo; de la Torre, Mercedes (Journal of Thoracic Disease; Vol 6, No 6 (June 26, 2014): Journal of Thoracic Disease, 2014)
Objectives: Conventional video-assisted thoracoscopic (VATS) lobectomy for advanced lung cancer is a feasible and safe surgery in experienced centers. The aim of this study is to assess the feasibility of uniportal VATS approach in the treatment of advanced non-small cell lung cancer (NSCLC) and compare the perioperative outcomes and survival with those in early-stage tumors operated through the uniportal approach. Methods: From June 2010 to December 2012, we performed 163 uniportal VATS major pulmonary resections. Only NSCLC cases were included in this study (130 cases). Patients were divided into two groups: (A) early stage and (B) advanced cases (>5 cm, T3 or T4, or tumors requiring neoadjuvant treatment). A descriptive and retrospective study was performed, comparing perioperative outcomes and survival obtained in both groups. A survival analysis was performed with Kaplan-Meier curves and the log-rank test was used to compare survival between patients with early and advanced stages. Results: A total of 130 cases were included in the study: 87 (A) vs. 43 (B) patients (conversion rate 1.1 vs. 6.5%, P=0.119). Mean global age was 64.9 years and 73.8% were men. The patient demographic data was similar in both groups. Upper lobectomies (A, 52 vs. B, 21 patients) and anatomic segmentectomies (A, 4 vs. B, 0) were more frequent in group A while pneumonectomy was more frequent in B (A, 1 vs. B, 6 patients). Surgical time was longer (144.9±41.3 vs. 183.2±48.9, P